Transport critical current density of Ag-sheathed Pr-doped (Tl, Cr)Sr2CaCu2O7 superconductor tapes in applied magnetic field - Lau, K.T. (Springer, 2002)
Powder-in-tube Tl-1212 (Tl,Cr)-Sr-(Ca,Pr)-Cu-O/Ag tapes were prepared and processed with different thermomechanical treatments. The processing conditions caused the variation of the transport critical current density (Jc) in the tapes. Tapes subjected to rolling showed lower Jc compared to the pressed tapes. Uniaxial pressing is more effective in densifying the tape cores by forcing the grains into closer contact and enhances the connectivity between grains. All the tapes showed a majority phase of 1212. The existence of 1201 phase considerably reduced Jc in the rolled tapes. Intermediate rolling is not favorable in improving Jc for the irregular grains structure, in contrast to Bi-2223 superconductors with plate-like grains. The in-field behavior of the tapes indicates that they are dominated by weak links as Jc falls rapidly in low applied field (H<0.06 T). No anisotropic transport properties were observed for all the tapes. SEM images showed randomly oriented irregular grains making texturing difficult to achieve. Neither the grain size nor the morphology was changed significantly by the thermomechanical treatments. The observed irregular grains imply that high-angle tilt boundaries were formed with intergranular weak links. Grain morphology is suggested to be the key factor that limits the Jc in these tapes.